Evaluation of magnetoelectric sensor systems for cardiological applications. (February 2018) - Reermann, Jens; Durdaut, Phillip; Salzer, Sebastian; Demming, Thomas; Piorra, André; Quandt, Eckhard; Frey, Norbert; Höft, Michael; Schmidt, Gerhard
Abstract: Thin-film magnetoelectric sensors are able to measure very low magnetic fields. As a consequence the hypothesis that magnetoelectric sensors could be used for biomagnetic measurements was often mentioned but never proven. In this contribution the first proof of this hypothesis will be given by the measurement of the (well-known) R-wave of the human heart. This will be achieved by closing the gap between the sensor sensitivity and the signal level by averaging. In order to guarantee a fast convergence of the averaging process even in very noisy (realistic) measurement environments, different adaptive averaging techniques in the time- and frequency-domain are pointed out. The evaluation by synthetic measurements shows an improvement of the averaging process by up to 20 dB in terms of signal-to-noise ratio for an instationary measurement scenario in comparison to the conventional averaging after 750 average periods. Finally, measurements of the R-wave of a human heart are performed.